Comparison of solar assisted heat pump solutions for office building applications in Northern climate. (March 2020) - Reda, Francesco; Paiho, Satu; Pasonen, Riku; Helm, Martin; Menhart, Florian; Schex, Richard; Laitinen, Ari
Abstract: Solar technologies can contribute to reaching the binding climate target of the Nordic countries. The application of two solar assisted solutions has been assessed for an office building located in Finland. The first one is a solar assisted absorption heat pump, which uses solar collectors and district heating as the main heating source. The other solution is a photovoltaic (PV) driven air source heat pump. The solar assisted absorption heat pump is able to upgrade the low temperature (5–10 °C) solar thermal energy into useful heat for building heating supply (renewable energy share of the heating season is about 19%), demonstrating that solar thermal energy can effectively contribute to supplying heat to buildings also in Northern European countries. The solar assisted absorption heat pump shows higher renewable energy share than the PV driven heat pump when comparing system solutions with the same area of installed solar technologies. However, the cost analysis shows that the electrically driven system is more economical viable. In a 15-year timescale, the cost of the electrically driven system is almost half of the thermally driven system. Therefore, costs of this solution have to considerably decrease to make solar assisted absorption heat pump competitive in Northern Europe. Highlights: Comparison of two solar assisted heat pump office building solutions. Solar absorption heat pump has higher renewable share than PV driven heat pump. The PV driven heat pump proved to be more economically viable. Solar absorption heat pump costs too high for being competitive in Nordic market.